Kamus Ilmu Biologi Berbasis Android - Norhayati, Norhayati; Ichsan, Mochammad Ichsan (STMIK Palangkaraya, 2017)
The need for education-themed applications, especially Biology subject that have the term Latin elusive and remembered by the public, especially the students who are studying Natural Sciences (IPA) in addition to the price of a dictionary of biology are relatively expensive complicate the students to buy. By the need of a dictionary and the use of communication devices such as smartphones based on android makes writers interested in creating a dictionary of biology-based android. This application is expected to provide ease in finding biological science terms by categories easily and less cost. Methods that are used in this study include data collection methods (interviews, literature methods, methods of documentation, the experimental method) and the method of system development.In this study, has successfully implemented a dictionary application android based biological term. The programming language PHP and the database used structured based Query Language (SQL) MySQL with kamus.sql name with three (3) tables. The writers applied the waterfall method of software development.